Legal Framework and Taxation Challenges on Digital Services in Indonesia: A Normative Legal Analysis - Rahmawati, Diah Ayu; Haryono, Haryono; Endarto, Budi; Sanusi, Ruchan; Prayogi, Yoga Adi (The Easta Journal Law and Human Rights, 2025)
The rapid expansion of digital services in Indonesia has introduced significant challenges to its legal and taxation frameworks. This study employs a normative legal analysis to explore gaps and inefficiencies in Indonesia's existing regulations, with a focus on the taxation of digital services. While initiatives such as VAT on digital goods and services (PMK 48/2020) have broadened the tax base, enforcement and compliance challenges persist, particularly for non-resident providers. Comparative analysis with global frameworks, such as the OECD’s Base Erosion and Profit Shifting (BEPS) initiative and the EU’s Digital Services Tax (DST), highlights potential pathways for reform tailored to Indonesia’s context. The study concludes with recommendations for harmonized legal frameworks, strengthened enforcement mechanisms, and policies balancing innovation with fair taxation. These reforms are essential for Indonesia to achieve a sustainable and equitable digital economy.